Drivers of Startups in Healthcare Sector: Evidence from Kingdom of Saudi Arabia - Bokhari, Rasha; Arafat, Mohd. Yasir; Qazi, Sayeeduzzafar (Journal of Posthumanism, 2025)
The Kingdom of Saudi Arabia is embarking on an ambitious journey towards economic diversification and a knowledge-based economy. Fostering a vibrant startup ecosystem is a key pillar of this transformation, with the healthcare sector presenting fertile ground for innovation. This research delves into the intricate web of factors that shape the creation of healthcare startups within the unique Saudi context. Drawing on empirical data and insights specific to the Saudi Arabian landscape, the study aims to shed light on the challenges and opportunities that healthcare startups encounter. It goes beyond simply identifying these factors; a nuanced analysis is conducted to understand the interplay between various influences. This multifaceted approach can provide invaluable knowledge for aspiring healthcare entrepreneurs, policymakers, and stakeholders invested in propelling the Saudi healthcare startup ecosystem forward. The research findings can empower key players to develop targeted support systems and initiatives. These can equip healthcare startups with the tools they need to navigate the intricacies of the Saudi market, fostering a new wave of innovation that ultimately improves healthcare delivery and accessibility for the region. By unveiling the complex landscape that shapes the Saudi healthcare startup scene, this research can serve as a valuable roadmap for stakeholders to cultivate a thriving ecosystem that fosters groundbreaking advancements in healthcare for the benefit of the Kingdom and beyond.